2013
DOI: 10.1371/journal.pone.0072839
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Risk Factors during Respiratory Infections in a Paediatric Ward in Antananarivo, Madagascar 2010–2012

Abstract: BackgroundAcute respiratory infections are a leading cause of infectious disease-related morbidity, hospitalisation and mortality among children worldwide, and particularly in developing countries. In these low-income countries, most patients with acute respiratory infection (ARI), whether it is mild or severe, are still treated empirically.The aim of the study was to evaluate the risk factors associated with the evolution and outcome of respiratory illnesses in patients aged under 5 years old.Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…They found no association between viral coinfection and length of stay, oxygen requirements, admission to PICU and need of mechanical ventilation [59]. They found a higher mortality risk in preschool children, which was not consistent with our results and previous studies [41,46]. The second systematic review with mixed adult-children population included 19 studies, and reported an overall increase in risk of hospitalization in patients with two or more viruses detected, but there was not a subgroup analysis only with children for this outcome [60].…”
Section: Discussioncontrasting
confidence: 95%
“…They found no association between viral coinfection and length of stay, oxygen requirements, admission to PICU and need of mechanical ventilation [59]. They found a higher mortality risk in preschool children, which was not consistent with our results and previous studies [41,46]. The second systematic review with mixed adult-children population included 19 studies, and reported an overall increase in risk of hospitalization in patients with two or more viruses detected, but there was not a subgroup analysis only with children for this outcome [60].…”
Section: Discussioncontrasting
confidence: 95%
“…However, influenza viruses seem to be only one of several frequent etiological agents of ILI: we found numerous other respiratory viruses, some in mono-infections and some in coinfections indicating that the circulation of these viruses in the community is substantial. As in Madagascar [16,17], pathogenic respiratory viruses were present in more than 70% of the samples collected from cases of ILI, and the involvement of non-influenza viruses was substantial: adenoviruses (22%), rhinoviruses (19%) (1) TAMBACOUNDA…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition-either hunger or obesity-is a risk factor for severe disease. In a study of outcomes among children hospitalized due to acute respiratory infection in Madagascar, 35 2 out of 3 malnourished children died. Disparities in vaccine uptake rates could also cause differential susceptibility once exposed to the virus.…”
Section: Differential Susceptibilitymentioning
confidence: 99%